Mapping the Informal Economy Around the World with an Enhanced MIMIC Approach: New Estimates for 110 Countries from 1997-2022 - Alban Asllani; Roberto Dell'Anno; Friedrich Schneider (CESifo GmbH, 2024)
Using an enhanced MIMIC method, this paper presents new estimates of the Informal Economy (IE) for 110 countries from 1997 to 2022. We address several limitations found in previous estimates of the IE, notably issues surrounding the missing values, time-invariant country characteristics, and calibration issues with exogenous variables. We enhance the MIMIC model by including fixed effects for country-specific characteristics of IE, thereby providing more reliable estimates. Our findings show a significant variation in the key drivers of IE between high-income and not-high-income countries, exhibiting distinct causal effects on the IE depending on different economic developments. In terms of normative implications, our results highlight the need for specific and tailored policies in dealing with the formalisation of informal activities in countries with different levels of income.
Keywords: O17; C39; H26; 330; informal economy; shadow economy; structural equation modelling; MIMIC approach